The concepts of the divine in the Greek magical papyri - Pachoumi, Eleni 1975-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2017)
Cover -- Preface -- Table of Contents -- List of Abbreviations -- Introduction: The Greek Magical Papyri -- I. General Character -- 1. Modern Editions and Translations -- 2. The History of Greek and Demotic Magical Papyri and Magical Handbooks -- II. Defixionum Tabellae and Magical Amulets -- III. Characteristics of the Greek Magical Papyri -- 1. Greek Language -- 2. Hymns -- 3. Categories of Spells -- 4. The Magical Operation -- IV. The Focus and Methods of the Monograph -- 1. Magic - Definition -- 2. The Concepts of the Divine in the Greek Magical Papyri: Chapter Description -- Chapter 1: The Religio-Philosophical Concept of the Personal Daimon and the Magico-Theurgic Ritual of Systasis -- I. Introduction -- II. The PGM Spells -- 1. "Systasis with your own daimon" (PGM VII.505-528) -- 2. Untitled spell for dream revelation (PGM VII.478-490) -- 3. Untitled spell concerning your own shadow (PGM III.612-632) -- 4. "The erotic binding spell of Astrapsoukos" (PGM VIII.1-63) -- III. Conclusion -- Chapter 2: The Religious Concept of Paredros -- I. Introduction - The Basic Concept of Paredros -- II. Paredroi as Daimones -- 1. "A daimon comes as an assistant" (PGM I.1-42) -- 2. "Power of the Bear constellation that accomplishes everything" (PGM IV.1331-1389) -- III. Paredros as the Resurrected Spirit and Body of the Dead -- A. Scholarly Discussion -- B. The issue of the resurrection of the dead in the spells -- 1. "King Pitys' spell that leads over any skull cup" (PGM IV.1928-2005) -- 2. "Divine assistance from three Homeric verses" (PGM IV.2145-2240) -- 3. "Pitys' spell that leads" (PGM IV.2006-2125) -- C. The purpose of reanimating the dead in the magical rite -- Conclusion -- IV. Paredros as the God Eros -- V. Paredros as the Spell Itself and as a God, or Goddess Revealed as Another Entity
1. "Spell of Pnouthis, the sacred scribe, for acquiring an assistant" (PGM I.42-195) -- 2. "Spell to Selene" (PGM I.147ff.) -- 3. Untitled spell to acquire a divine assistant (PGM LVII.1-37) -- 4. The "Lunar spell of Klaudianus and ritual of heaven and the Bear constellation over lunar offerings" (PGM VII.862-918) -- 5. "The old serving woman of Apollonius of Tyana" (PGM XIa.1-40) -- Conclusion -- VI. Paredros as Divine Assistance from Homeric Verses and an Object -- VII. The Relationship between the Paredros and the Magician -- VIII. Conclusion -- Chapter 3: The Concept of God through Manifold Religious and Philosophical Assimilations -- I. Introduction -- II. Helios -- 1. "Spell to bring the god" (PGM IV.985-1035) -- a) Helios the greatest god, lord Horus Harpocrates -- b) Helios holding the reins and steering the tiller, restraining the serpent -- c) Helios - praised, Iao -- 2. "This is the (consecration) ritual for all purposes. Spell to Helios" (PGM IV.1596-1715) -- d) Helios - the gracious Good Daimon -- e) Helios - Sabaoth Adonai, the great god -- f) Helios - the Cosmokrator, the Thalassokrator, Heaven as Helios 'processional way -- 3. "[Systasis to] Helios" (PGM III.494-611) -- g) Helios - the image, the whole of the cosmos -- forms and names -- 4. "Systasis with your own daimon" (PGM VII.505-528) -- h) Helios - the Mixture of the Cosmic Nature -- 5. Hymn "To Helios" (PGM IV.939-948) -- i) Helios - ϕυσικαὶ πυρὸς ἀρχαί or ϕύσι καὶ πυρὸς ἀρχή -- Conclusion -- III. Eros -- 1. "Eros as an assistant" (PGM XII.14-95) -- Conclusion -- 2. "The sword of Dardanos" (PGM IV.1716-1870) -- Conclusion -- IV. The Creator-God -- 1. "Prayer of Jacob" (PGM XXIIb.1-26) -- 2. "Oracle of Kronos demanding, called little mill" (PGM IV.3086-3124) -- 3. "[Systasis to] Helios" (PGM III.494-611) -- 4. "The sword of Dardanos" (PGM IV.1716-1870)
5. "A little ring" (PGM XII.201-269) -- 6. The use of κτίζω -- Conclusion -- V. Aion -- 1. "Divine assistance from three Homeric verses" (PGM IV.2145-2240) -- 2. "GOD/GODS -- A sacred book called Monad or Eighth Book of Moses about the holy name" (version A.1-343 from PGM XIII.1-734) -- 3. "A little ring" (PGM XII.201-269) -- 4. "Stele" (PGM IV.1167-1226) -- 5. "Another way" (PGM V.459-489) -- Conclusion -- VI. Chrestos -- 1. "Releasing from bonds" (PGM XIII.288-295) -- a) Orthographical and interpretation issues: The scholarly discussion -- b) Analysis of the spell - Influences and Religious Assimilations -- i) Chrestos as the creator -- ii) Chrestos as "the one who created Compulsion and Punishment and Torture" -- iii) The "release" and "open-up" formula -- iv) Chrestos "biaios": Mechanisms of appropriation and integration -- Conclusion -- VII. Dionysus-Osiris -- A. Osiris -- 1. "Pitys' spell that leads" (PGM IV.2006-2125) -- B. Dionysus -- i) Explicit references to Dionysus -- 1. Untitled Spell (PGM XIII.734-1077) -- ii) Allusions to Dionysus -- 1. "A daemon comes as an assistant" (PGM I.1-42) -- 2. "Excellent philtron" (PGM VII.459-461) -- 3. "Cup spell" (PGM VII.643-651): Dionysus-Osiris Assimilation -- 4. "This is the (consecration) ritual for all purposes. Spell to Helios" (PGM IV.1596-1715) -- Conclusion -- VIII. Hekate-Selene-Artemis -- 1. "Prayer to Selene" (PGM IV.2785-2890) -- 2. "Erotic spell that leads" (PGM IV.2441-2621) -- Conclusion -- IX. Hermes-Thoth-Hermes Trismegistos -- A. Hermes-Thoth -- B. Hermes Trismegistos -- C. The Religious and Philosophical Assimilations -- 1. Untitled spell for revelation (PGM V.370-446) -- 2. "The erotic binding spell of Astrapsoukos" (PGM VIII.1-63) -- 3. "Lamp divination" (PGM VII.540-578) -- Conclusion -- X. Typhon-Seth -- A. The symbolism of the blood of Typhon-Seth
B. The Religious and Philosophical Assimilations -- 1. "Spell to restrain anger and to subject" (PGM VII.940-968) -- 2. "Nephotes to Psammetichos immortal king of Egypt" (PGM IV.154-285) -- 3. "Spell to restrain" (PGM XXXVI.1-34) -- 4. Untitled spell (PGM XIVc.16-27)/"Spell to cause 'evil sleep'" (PDM xiv.675-694) -- 5. "Separation spell" (PGM XII.365-375) -- Conclusion -- XI. Sarapis -- 1. Untitled erotic spell (PGM XIXa.1-54) -- 2. "Oracle of Sarapis" (PGM V.1-53) -- 3. "This is the (consecration) ritual for all purposes. Spell to Helios" (PGM IV.1596-1715) -- 4. "Another way" (PGM V.459-489) -- Conclusion -- XII. Isis -- 1. "The erotic binding spell of Astrapsoukos" (PGM VIII.1-63) -- 2. Untitled spell to acquire an oracle (/"Great Isis the lady") (PGM XXIVa.1-25) -- 3. Untitled spell for protection (Φυλακτήριον) (PGM VII.490-504) -- 4. Untitled spell to acquire a divine assistant (PGM LVII.1-37) -- Conclusion -- XIII. Aphrodite -- 1. "Erotic spell that leads" (PGM IV.2891-2942) -- 2. "Aphrodite's name" (PGM IV.1265-1274) -- Conclusion -- XIV. Bes(as) -- 1. Spells: "Request for a dream oracle from Besas" (PGM VII.222-249) and "Request for the dream oracle of Besas" (PGM VIII.64-110) -- 2. "Stele of Jeu the hieroglyphist in his letter" (PGM V.96-172, IV C.E.) -- 3. "A restraining seal" (PGM IV.2125-2139, IV C.E.) -- Conclusion -- XV. Divine Epithets and Identities -- XVI. Conclusion -- Epilogue -- Appendix 1 -- Table 1: List of PGM and PDM -- Table 2: PGM and PDM Handbooks -- Table 3: PGM and PDM Texts -- Appendix 2 -- Appendix 3 -- PGM Hymns -- Appendix 4 -- Homeric Lines Copied in PGM -- Appendix 5 -- Magicians, or other Figures Engaged with Magic in the PGM -- Appendix 6 -- A List of Epithets Recorded in the LSJ and LSJ Supplements as Particularly Found in the PGM -- Appendix 7
A List of Epithets from the PGM that are not recorded in the LSJ and LSJ Supplements -- Bibliography -- Index of Greek Words -- Index of Sources -- Ostraca, Papyri, Tablets -- Oracula Chaldaica (Orac. Chald.) -- Orphica -- Homeric Hymns (Hymn. Hom.) -- Corpus Hermeticum (Corp. Herm.) -- Nag Hammadi -- Greek, Roman, Jewish and Christian Authors -- Old Testament (Septuagint) -- Old Testament Apocrypha -- New Testament -- New Testament Apocrypha -- Index of Modern Authors -- Index of Names and Subjects
Keywords: Magic, Egyptian; Electronic books